Assessing the impact of AI influencers on customer engagement for non-luxury brands in Egypt - Abdelrazek, Nesma Ibrahim Amir; Khalil, Alaa Tarek (Journal of Economic, Administrative and Legal Sciences, 2024)
Purpose: In this study we will examine the impact of AI influencers on customer engagement for non-luxury brands in Egypt. Objective: The main objective of this study is to assess the impact of AI influencers on the engagement of customers especially for non-luxury brands field and to study the impact of AI influencers on WOM, trust and following intentions.Methodology/Design/Approach: Through literature review and a very limited exploratory study depending on personal interviews with a mix of experts and customers, the study disclosed that the impact of AI influencers on the engagement of customers with the luxury brands has a positive impact but a limited impact on customer engagement for non-luxury brands especially the Egyptians who do not consider AI influencers as a trust source of information. Value: This study offers some perceptions into the impact of AI influencers on customer engagement especially for non-luxury brands which will update the existing literature review within the field of non-luxury brands.This study’s findings can provide marketers with some new insights for how to deal with the new marketing trends and to help them upgrade their job experiences on starting to deal with AI influencers and create their own one instead of social media influencers.
Keywords: Influencers; AI Influencers; Customer Engagement; Non-Luxury Brands; Brand Loyalty; WOM; Purchase Intention